4CPS-172 Posaconazol therapeutic drug monitoring in a paediatric tertiary hospital. (23rd March 2022) - Font, A; Arrojo, J; Comes, A; Mas, N; Sanchez, M; Vinent, J
Abstract : Background and importance: Invasive fungal infections (IFI) are a major cause of morbidity and mortality in immunosuppressed patients. Posaconazole is used for prophylaxis and treatment of IFI in immunocompromised patients, although there are scarce data on its pharmacokinetics and posology in children. Posaconazol dosing schedule of our institutional protocol for IFI prophylaxis is 4 mg/kg (max 400 mg) three times a day and 6 mg/kg (max 300 mg) once daily (twice daily on day 1) for oral suspension and tablets, respectively. Aim and objectives: Determine the number of patients who achieved therapeutic plasma concentrations at steady state (ssCp) (0.7–3.75 µg/mL) with the dosing schedule of our institutional protocol. Describe and analyse the pharmaceutical interventions necessary to achieve optimal ssCp and avoid toxicities or treatment failure. Material and methods: Retrospective, observational, single-centre study including 103 immunocompromised patients receiving prophylactic posaconazole from April 2020 to September 2021, with a treatment duration of at least 1 week. Variables collected: age, weight, formulation and trough ssCp. Results: The patients had a median age of 9 (2–23) years and a mean weight of 33.6±18.3 kg. 57/103 (55.3%) of the patients received suspension and 46/103 (44.7%) tablets. 71/103 (68.9%) of the patients had ssCp within the therapeutic range after the first draw (suspension, 31/71; tablets, 40/71), 23/103(22.4%) had a ssCp value <0.7 (suspension, 12/23; tablets, 11/23) and 9/103 (8.7%) had a ssCp value >3.75 (suspension, 4/9; tablets, 5/9). 356 pharmaceutical interventions were performed, 151 in patients taking oral suspension and 205 receiving tablets. In the first group, the dose was decreased in 10.6% of interventions, increased in 23.2% and 61.6% did not require dose changes; treatment was discontinued in 4.6% due to drug interactions, toxicity or change of therapy. Regarding those receiving tablets, the recommendation was to reduce the dose in 11.7%, not to change in 76.1%, increase in 7.8% and stop in 4.4%. In some cases dose modifications were made for clinical circumstances. Conclusion and relevance: Most patients achieved therapeutic ssCp after the first determination according to our scheme.The need for dose adjustments was more frequent among the suspension group in order to achieve a correct ssCp, which is consistent with adult and paediatric population studies. Hence, it shows the relevance of pharmacokinetics studies of posaconazole in paediatric populations and the lack of evidence to ensure its efficacy and safety. References and/or acknowledgements: Conflict of interest: No conflict of interest